Quality of care predicts outcome in systemic lupus erythematosus: a cross-sectional analysis of a German long-term study (LuLa cohort). (February 2020) - Kernder, A; Richter, J G; Fischer-Betz, R; Winkler-Rohlfing, B; Brinks, R; Schneider, M; Chehab, G
Objective: Our aim was to study the quality of medical care in patients with systemic lupus erythematosus (SLE) to understand gaps and to analyze the association with outcome of the disease. Methods: Information on demographics and medical care was assessed by self-reported questionnaires among SLE patients (LuLa cohort, 2011, n  = 580). In total, 21 aspects of medical care were analyzed. Univariate analysis selected 10 predictor variables for further analysis: (1) urine examination and (2) blood test in the previous year, (3) taking antimalarials, (4) taking vitamin D and calcium if the dosage of prednisolone was greater than 7.5 mg/day, counseling regarding (5) lipid metabolism, (6) vaccination, and (7) blood pressure, and treatment of the comorbidities (8) hypertension, (9) osteoporosis and (10) lipid metabolism disorder. The association of these 10 items with the outcome of the disease, assessed in 2015, was analyzed by linear regression analysis, adjusted for age, disease duration and sex. Results: On average six of the 10 items were met (±1.7). Receiving more clinical care in 2013 was predictive for low disease activity (SLAQ, p  = 0.024, β = –0.104, corr. R 2  = 0.048), low progress in disease-related damage (Delta Brief Index of Lupus Questionnaire, p  = 0.048, β = –0.132, corr. R 2  = 0.036) and high health-related quality of life (SF-12 physical, p  = 0.035, β = 0.100, corr. R 2  = 0.091) in 2015. Conclusion: Our study illustrates a link between the quality of care and the SLE outcome parameters disease activity, disease-related damage and quality of life. Consistent considerations of these care parameters, which are recommended in several management guidelines, could therefore be a good approach to improve the outcome of patients with SLE.